Can fintech promote environmental investment in heavily polluting enterprises? evidence from China - Zhang, Xiao; Zhao, Yu; Liu, Xiaoyu (Frontiers in Environmental Science, 2024)
Environmental pollution has long been a global concern, and the development of fintech has led to radical changes in the financial industry, while finance plays a very important role in environmental governance. We use the number of fintech companies to create a city fintech index, and with the data of 827 listed companies in heavily polluting industries from 2011 to 2020, we study the impact of fintech development on enterprise environmental investment. We find that fintech can significantly increase the environmental investment of heavily polluting enterprises, while increasing the size of enterprise green bonds and improving the green cognition of executives are two important influence mechanisms. Heterogeneity analysis found that the impact of fintech on Southern enterprises and stateowned enterprises is more significant. Further analysis shows that fintech can significantly reduce the carbon emissions of heavily polluting enterprises and increase the number of green invention patents. The results of the study provide a useful reference for the government to promote the implementation of fintech policies and explore new ways to modernize pollution management.